علاقات الحمل على النّظير في التراكيب العربية: مقاربة في منوال البنية مع الوظيفة - عباس, عبد الرؤوف (جامعة الوادي - University of Eloued, 2016)
لكل قسم من أقسام الكلام ما يناظره مما يقع موقعه في التركيب أو يحل محله في الرتبة العاملية، فجاء هذا المقال ليوجّه هذه العلاقة في أقوال النحاة مركّزا على قضيتين اثنتين هما: البنية والوظيفة، الأولى تحدّد رتبة التراكيب عامليا، والثانية توضّح وظيفتها الخطابية، وتم خلاله معاجة هذه العلاقة ضمن جملة من المصطلحات العلمية النحوية انطلاقا من الحمل على النّظير بوصفه مصطلحا أصوليا، ووصولا إلى العامل بوصفه يرتبط بجملة أخرى من المصطلحات كالبنية والباب والمجرى والأصل والفرع Summary article : The summary of what This article seeks to his statement and prove is that every linguistic structures dating back to the origin of filial one, and this study was based on the matching between the installation camel career goal in its simplest form in the (beginner and news) and installation filial goal of (factor applicable), and then get the rest of compositions functional language for being isotopes for this installation on this first construction was originally deemed to have a branch with him Our study in this article will be based on the identification of the two grammarians in linguistic structures: The first element is the installation grammar: The determination of the grammarians of the concept of wholesale proceeds from the reality of the speech or verbal event, they are less so ineffable and silent upon a valuable series of words useful The second element is in place and working: The first factor is closely linked in our government necessary
مقال
Keywords: الحمل على النظير، التراكيب العربية، منوال البنية مع الوظيفة